3D Electronic Channels Wrapped Large‐Sized Na3V2(PO4)3 as Flexible Electrode for Sodium‐Ion Batteries. Issue 43 (22nd January 2018) - Ni, Qiao; Bai, Ying; Li, Yu; Ling, Liming; Li, Limin; Chen, Guanghai; Wang, Zhaohua; Ren, Haixia; Wu, Feng; Wu, Chuan
Abstract: The development of portable and wearable electronics has aroused the increasing demand for flexible energy‐storage devices, especially for the characteristics of high energy density, excellent mechanical properties, simple synthesis process, and low cost. However, the development of flexible electrodes for sodium‐ion batteries (SIBs) is still limited due to the intricate production methods and the relatively high‐cost of current collectors such as graphene/graphene oxide and carbon nanotubes. Here, the hierarchical 3D electronic channels wrapped large‐sized Na3 V2 (PO4 )3 is designed and fabricated by a simple electrospinning technique. As flexible electrode material, it exhibits outstanding electrolyte wettability, together with ultrafast electronic conductivity and high Na‐ion diffusion coefficients for SIBs, leading to superior electrochemical performances. A high reversible specific capacity of 116 mA h g −1 (nearly 99% of the theoretical specific capacities) can be obtained at the current density of 0.1 C. Even after a 300‐fold current density increased (30 C), the discharge specific capacity of the flexible electrode still remains 63 mA h g −1 . Such an effective concept of fabricating 3D electronic channels for large‐sized particles is expected to accelerate the practical applications of flexible batteries at various systems. Abstract : Polyacrylonitrile is used for electrospinning with Na3 V2 (PO4 )3 (NVP), to form 3D electronic channels wrapped large‐sized flexible NVP materials, which can be directly used as cathode for sodium‐ion batteries without binder, conductive carbon, and current collector, thus the electronic conductivity and rate performances are significantly promoted.